Effect of a six-week-intervention with an activitypromoting video game on isometric muscle strength in elderly subjects - Sohnsmeyer, J.; Gilbrich, H.; Weisser, B. (International Journal of Computer Science in Sport, 2010)
In order to analyze the effect of a six-week intervention with an activitypromoting video game on muscle strength in elderly subjects (> 60 years) a controlled pretest-posttest study was conducted. The intervention group performed a 20-minutes session playing Wii bowling, twice a week for a total of six weeks. Data was analyzed by use of an ANCOVA. When comparing the results with the control group findings, the isometric muscle strength of the m. quadriceps increased significantly. Thus, an activitypromoting video game such as bowling with a Wii leads to functional improvement and might have positive health implications for elderly people.